Asymptomatic Pyuria In Diabetic Females - Nasir, Hussein Aziz (Journal of the Faculty of Medicine Baghdad, 2006)
Background: The goal of this study was to determine the prevalence and the risk factors of asymptomatic pyuria in diabetic female patients. Methods: The study included 100 diabetic female patients and 100 non diabetic females attending the outpatient in the period from Sep.2001 to Sep.2002.Patients with symptoms of urinary tract infection were excluded. Asymptomatic pyuria was defined as the presence of more than 10 leukocytespower field in an uncentrifuged random urine sample. Results: Diabetic women more often had asymptomatic pyuria than non diabetic women. The prevalence of asymptomatic pyuria was significantly higher in patients with duration of diabetes exceeding 15 years than those below. Diabetic females with asymptomatic pyuria more often had diabetic retinopathy, neuropathy, nephropathy, cerebrovascular disease, and ischemic heart disease than those without asymptomatic pyuria. As the degree of neuropathy increases it is accompanied by an increase in the prevalence of asymptomatic pyuria. The prevalence of asymptomatic pyuria was significantly increased in patients with proliferative diabetic retinopathy. As degree of nephropathy increases, it is accompanied by an increase in the prevalence of asymptomatic pyuria, Conclusion: There is an increase in the prevalence of asymptomatic pyuria among diabetic females with complications of retinopathy, neuropathy and in nephropathy. The prevalence of asymptomatic pyuria increased with long duration of diabetes as diabetic microangiopathy becomes sever.